Water treatment : principles and design. - Crittenden, John C., ....-; Hand, David W., ....-; Rhodes Trussell, R., ....- (Hoboken : Wiley, 2005)
1 Introduction 2 Physical and chemical quality 3 Microbiological quality 4 Water quality management strategies 5 Fundamentals of chemical reactions 6 Reactor analysis 7 Introduction to separation processes and mass transfer 8 Chemical oxidation and reduction 9 Coagulation, mixing, and flocculation 10 Gravity separation 11 Granular filtration 12 Membrane filtration 13 Disinfection 14 Air stripping and aeration 15 Adsorption 16 Ion exchange 17 Reverse osmosis 18 Disinfection/oxidation byproducts 19 Removal of selected constituents 20 Residuals management 21 Internal corrosion of water conduits 22 Synthesis of treatment trains : case studies from bench to full scale App. A Conversion factors App. B Physical properties of selected gases and composition of air App. C Physical properties of water App. D Federal regulations that pertain to drinking water App. E Summary information for advanced oxidation App. F U.S. Environmental Protection Agency Ct values for various disinfectants App. G Adsorption isotherm parameters K and 1/n for liquid phase App. H Atomic weights
Keywords: Waterzuivering